Propolis: Antineoplastic Activity, Constituents, and Mechanisms of Action - Ruiz-Bustos, Patricia; Alday, Efrain; Garibay-Escobar, Adriana; Sforcin, José Maurício; Lipovka, Yulia; Hernandez, Javier; Velazquez, Carlos (Current Topics in Medicinal Chemistry, 2023)
Propolis is a beehive product with great pharmacological potential, including antineoplastic activity. Objectives: The aim of this study is to provide an actual understanding of the existent scientific information regarding the antiproliferative effect of propolis, proposed mechanisms of action, and challenges to meet. Methods: An assessment of the scientific literature was attained using the PubMed and SciFinder platforms. Research papers, clinical trials, and reviews published between the years 2000 - 2021, were considered. The words “anticancer”, “antitumor”, “antiproliferative” and “propolis” were used in the search criteria. Conclusion: A summary of several antiproliferative activities of different types of propolis is exposed. The potential health benefits of propolis are discussed. The variable plant origin of propolis partially accounts for its anti-cancer activities. Even when some mechanisms of action of propolis have been proposed, much of the genesis of how this effect is produced is yet to be answered, including several molecular mechanisms in different biological systems.
Keywords: Anticancer